Workplace bullying and its effect on employee well-being in Ghana’s oil and gas industry - Kumako, Stephen Kodjo (2019)
The World Health Organisation (2017) asserts that changes in the world of work have resulted in new risks to employee health and safety. The focus of occupational health and safety professionals has evolved beyond physical risks, and now includes psychosocial risks such as workplace bullying. Workplace bullying is an extreme social stressor that has the potential to affect victims, witnesses, co-workers, significant others, the organisation itself and society. Whilst much is known about this phenomenon in other parts of the world, very little research effort has examined workplace bullying in Sub-Saharan African countries such as Ghana. Accordingly, this thesis aimed at understanding the lived experiences of employees in the nascent oil and gas industry in Ghana. Furthermore, this research sought to apply the Job Demands-Resources model to workplace bullying and test an adapted theoretical model based on Einarsen et al.’s (2011) comprehensive model of workplace bullying.